Protective Role of Rabbit Nucleotide-Binding Oligomerization Domain-2 (NOD2)-Mediated Signaling Pathway in Resistance to Enterohemorrhagic Escherichia coli Infection - Guo, Mengjiao; Li, Rong; Xiao, Qianqian; Fan, Xiuxiu; Li, Ning; Shang, Yingli; Wei, Liangmeng; Chai, Tongjie (Frontiers in Cellular and Infection Microbiology, 2018)
Nucleotide-binding oligomerization domain 2 (NOD2), a member of the NOD-like receptors family that is well known to play a key role in innate immune responses and is involved in innate antibacterial responses. In this study, rabbit NOD2 (rNOD2) was cloned from rabbit kidney cells. It was distributed in various tissues, and the highest level of rNod2 was detected in spleen. Moreover, the expression of rNod2 was significantly upregulated in the heart, liver, and spleen induced by enterohemorrhagic Escherichia coli (EHEC). Overexpression of rNOD2 induced the expression of pro-inflammatory cytokine, including Il1β, Il6, Ifn-γ, and Tnf, as well as defensins, including Defb124, Defb125, and Defb128 through the nuclear factor (NF)-κB signaling pathway. Furthermore, overexpression of rNOD2 inhibited the growth of EHEC, and knockdown of rNOD2 or inhibition of the NF-κB pathway promoted its replication. In addition, our results suggest that rNOD2 can significantly activate NF-κB signaling and trigger antibacterial defenses to increase the expression of pro-inflammatory cytokine and defensins after stimulation by EHEC. These findings are useful to further understanding the innate immune system of rabbits and providing a new perspective for the prevention of bacterial diseases in rabbits.